Handbook of Clinical Hypnosis. 1993
DOI: 10.1037/10274-027
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatment of warts.

Abstract: Numerous case studies and several experiments have indicated that suggestive procedures may be effective in treating a variety of dermatological disorders, including congenital ichthyosiform erythrodermia of Brocq (fish skin disease; Mason, 1955; Wink, 1961), psoriasis (Frankel & Misch, 1973, genital herpes (Longo, Clum, &Yaeger, 1988), and warts (e.g., Couper &Davies, 1952;Obermayer & Greenson, 1949). Some dermatological disorders, such as fish skin disease, are so rare as to preclude multisubject experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The effect of a hypnotic induction is to increase responsiveness to these suggestions, but only to a surprisingly small degree ("far less than the classical hypnotists would have supposed had the question ever occurred to them," wrote Clark Hull [1933, p. 298]) and only for a minority of subjects (Barber & Glass 1962;Hilgard & Tart 1966;Hull 1933;Stam & Spanos 1980;Weitzenhoffer & Sjoberg 1961). Suggestion without hypnosis has even been found to reduce warts (DuBreuil & Spanos 1993) and control pain during surgery without anesthesia ( Jones 1999).…”
Section: Hypnosis and Willmentioning
confidence: 99%
“…The effect of a hypnotic induction is to increase responsiveness to these suggestions, but only to a surprisingly small degree ("far less than the classical hypnotists would have supposed had the question ever occurred to them," wrote Clark Hull [1933, p. 298]) and only for a minority of subjects (Barber & Glass 1962;Hilgard & Tart 1966;Hull 1933;Stam & Spanos 1980;Weitzenhoffer & Sjoberg 1961). Suggestion without hypnosis has even been found to reduce warts (DuBreuil & Spanos 1993) and control pain during surgery without anesthesia ( Jones 1999).…”
Section: Hypnosis and Willmentioning
confidence: 99%
“…Barber's (1965) literature review revealed that hypnotic suggestion has been associated with reports of changes in such "unchangeable" bodily processes as the nonsurgical removal of warts and rapid recovery from burns, one of them a third-degree burn of a type so severe that skin grafting is typically required (Ewin, 1978). DuBreuil and Spanos (1993) reported data that "hypnotic suggestions produce wart remission that cannot be accounted for in terms of spontaneous remission" (p. 637). DuBreuil and Spanos also used nonhypnotic imagery as a successful treatment for wart remission.…”
Section: Biological Markers and Psychophysiological Characteristicsmentioning
confidence: 99%